Ribosomal RNA Synthesis in Soybean Suspension Cultures Growing in Different Media - Jackson, Paul J. (1982)
The transcription of ribosomal RNA has been studied in suspension tissue cultures of soybean Glycine max L. Merr cv. Mandarin cells (SB-1). A large precursor molecule was synthesized which contains RNA homologous to the 25 and 18S cistrons. Transcription was from one strand and appeared to start adjacent to the 18S cistron and to proceed through the 18S DNA, a <0.6-kilobase transcribed spacer and the 25S cistron. A nontranscribed spacer region was identified. When cells grew rapidly in sucrose (24 hours doubling time) they contained 7 times as many ribosomes as when they grew slowly in maltose (200 hours doubling time). Upon transfer from maltose to sucrose, cells began to accumulate ribosomes at a rapid rate (80-fold more rapid synthesis than in maltose medium) within 2 hours at 33°C. The 2-hour lag is due in large part to a longer processing time during which newly synthesized RNA is packaged into ribosomes. Therefore, the increase in transcription rate may occur within a few minutes of the transfer to sucrose.